2011
DOI: 10.3109/17453674.2011.618919
|View full text |Cite
|
Sign up to set email alerts
|

Genetic epidemiology of Scheuermann's disease

Abstract: Background and purposeThe genetic/environmental etiology of Scheuermann's disease is unclear. We estimated the heritability of the disease using an etiological model adjusted for sex and time of diagnosis, and examined whether the prevalence of Scheuermann's disease was constant over time.Methods46,418 twins were sent a questionnaire about health and disease. Of these, 75% returned the questionnaire and 97% answered the question “Have you been diagnosed as having Scheuermann's disease by a doctor?”ResultsRespo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 17 publications
2
35
0
2
Order By: Relevance
“…Indeed, the most common forms of kyphosis and scoliosis in adolescents are nonsyndromic and include: Scheuermann disease3 a form of nonsyndromic kyphosis, which affects >8% of the population12; idiopathic scoliosis (IS), which affects approximately 2% to 3% individuals13, 14, 15, 16; and congenital nonsyndromic scoliosis, which is reported to have a prevalence of approximately 0.5 to 1 per 1000 individuals 9. Familial and twin studies have indicated a genetic basis for kyphosis17, 18, 19, 20 and scoliosis,21, 22, 23, 24, 25, 26, 27, 28 with likely genetic heterogeneity. However, studies aimed at defining the genetic abnormalities causing these spinal disorders have been hampered by their phenotypic and genetic heterogeneity, variable modes of inheritance,8, 29 and gene‐environment interactions that may modify the phenotypic expression 9.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the most common forms of kyphosis and scoliosis in adolescents are nonsyndromic and include: Scheuermann disease3 a form of nonsyndromic kyphosis, which affects >8% of the population12; idiopathic scoliosis (IS), which affects approximately 2% to 3% individuals13, 14, 15, 16; and congenital nonsyndromic scoliosis, which is reported to have a prevalence of approximately 0.5 to 1 per 1000 individuals 9. Familial and twin studies have indicated a genetic basis for kyphosis17, 18, 19, 20 and scoliosis,21, 22, 23, 24, 25, 26, 27, 28 with likely genetic heterogeneity. However, studies aimed at defining the genetic abnormalities causing these spinal disorders have been hampered by their phenotypic and genetic heterogeneity, variable modes of inheritance,8, 29 and gene‐environment interactions that may modify the phenotypic expression 9.…”
Section: Introductionmentioning
confidence: 99%
“…(2,4) The etiology is controversial, but factors such as hormonal changes, circulatory disorders and genetic factors appear to influence the onset of the disease. (2,5) The diagnosis is made by X-rays in profile was considered positive when at least three adjacent vertebrae submit a previous larger than 5° wedging. Scoliosis and decreased intervertebral joint space can also be found as radiological changes.…”
Section: Introductionmentioning
confidence: 99%
“…(3) occurs between 10-12 years of age and is characterized by the anterior plate disorder growth of the vertebral body, leading to deformity in kyphosis. (2) There is a decrease of physical fitness induced deformity, and social isolation, making the integration of these adolescents in society. (2,4) The etiology is controversial, but factors such as hormonal changes, circulatory disorders and genetic factors appear to influence the onset of the disease.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations